Individualizatsiya - bazhnejshaya problema sporta vysshikh dostizhenij - Zaporozhanov, V. A. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
Individualization in elite sport training - In april, 2002, an international symposium about this problem took place at Gdansk (Poland). The three main complexes of the work there were: 1. theoretical-methodological basics of sports training 2. medico-biological and psychological basics for the individualisation of training 3. methods of complex control of individual training process